Investigation of FR4 Substrate Effects on Elliptical Patch Antenna Design for 5G Applications - Akande Ademola,; Fawole Ayobami,; Olayiwola Olanike. G,; Kolawole Tolulope,; Adeniji Aderogba, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid development of fifth-generation (5G) networks necessitates high-performance antennas with optimized radiation characteristics. This study investigates the effect of the FR4 substrate on the performance of an elliptical patch antenna designed for 5G applications. Using MATLAB, key antenna parameters, including return loss, voltage standing wave ratio (VSWR), impedance matching, directivity, and gain, were analyzed. The results indicate that the elliptical antenna with FR4 substrate operates optimally at 3.57 GHz, achieving a bandwidth of 0.24 GHz at -5 dB. The VSWR value at 3.5 GHz was found to be 1.623, confirming good impedance matching. The estimated impedance for FR4 was 90 Ω, ensuring efficient power transfer. Directivity measurements yielded values of -0.9 dB and 4.1 dB along the azimuth and elevation planes, respectively. These findings highlight FR4’s suitability for cost-effective 5G antenna designs, offering a balance between performance and affordability. This study provides valuable insights into substrate selection for optimal antenna efficiency in 5G communication systems.
Keywords: 5G networks; elliptical patch antenna; FR4 substrate; MATLAB; return loss; VSWR; Impedance Matching; Directivity; Antenna Gain; Substrate Selection